Upgrade of electronics of neutron monitors DOMC and DOMB - Poluianov, Stepan; Usoskin, Ilya; Du Toit, Straus (2021)
DOMC and DOMB neutron monitors (NM) operate at the Concordia research station (Dome C on the Antarctic plateau, 75 o 06’S, 123 o 23’E, 3233 m a.s.l.) since 2015. Their high elevation and proximity to the geomagnetic pole provide low atmospheric and geomagnetic cutoffs and, therefore, the exceptionally high sensitivity to low-ener- gy cosmic rays. The instruments are the so-called mini neutron monitors with BF 3 -filled counter tubes. DOMC has the standard design with a lead neutron multiplier and DOMB is a so-called “bare” (lead-free) unit. We report on a recent upgrade of the electronics heads of these instruments. The new heads have a modular architecture, built upon a single-board computer Raspberry Pi. The upgrade increases the capabilities of the instruments in two aspects: (1) measurements, particularly, of cosmic ray multiplicity; (2) remote control and monitoring. The new electronic heads register each pulse from a detector, giving a timestamp with microsecond precision, which is crucial for multiplicity measurements. Many important parameters (e.g., high voltage, pulse detection thres- holds) can be controlled and adjusted remotely with the new design. High computing power allows performing data processing on the fly. The upgrade increases the capability of DOMC and DOMB in cosmic ray measurements and improves control of the operation of the neutron monitors.